UPAYA MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA BERHITUNG PENGURANGAN MELALUI MODEL PROBLEM BASED LEARNING SISWA KELAS 1 SDN JALUPANG - Refiani Mardia Kurniawati; Moh. Fadli (Jurnal Riset Pendidikan Dasar Dan Karakter, 2025)
This study aimed to improve first-grade students’ motivation and learning outcomes in subtraction through the implementation of the Problem-Based Learning (PBL) model. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The participants were 31 students of SDN Jalupang. Data were collected through observation, documentation, and story-based subtraction tests. The findings indicated progressive improvement across cycles. In Cycle I, the average score was 65 with 65% of students achieving mastery. In Cycle II, the average score increased to 76 with 90% mastery. These results demonstrate that the implementation of PBL effectively enhances students’ motivation and learning outcomes in subtraction. The PBL model promotes active student engagement in contextual problem-solving, making learning more meaningful